Estudio de prefactibilidad del montaje de un centro radiológico en la ciudad de Barranquilla. (2022)
The present work is developed in order to carry out a complete analysis for the implementation of a radiology center focused on dental health in the center of the city of Barranquilla, seeking to provide greater coverage to the population since a low number of centers is evident. dental radiology with respect to the demand for patients referred by dental offices; The implementation of the radiological center seeks to have a positive impact within the health sector by providing high quality, efficiency and state-of-the-art technology with affordable prices to the target population seeking an excellent service to citizens. For the purpose of the object of this work, market, financial and technical studies will be carried out to determine the viability of the project, these studies will facilitate the evaluation of each of the requirements and requirements necessary to argue the pre-feasibility for prospective investors.